Deep Brain Stimulation for Treatment-Refractory Depression. Issue 11 (November 2016) - Narang, Puneet; Retzlaff, Amber; Brar, Kanwarjeet; Lippmann, Steven
Abstract : Abstract: Depression has a high lifetime prevalence and recurrence rate, with more than one-third of affected patients experiencing treatment-refractory depression. These individuals should benefit from additional treatment options such as deep brain stimulation (DBS), a research-grade intervention. DBS is being investigated for its efficacy in treatment-refractory cases. We reviewed the English-language literature published between the years 2010 and 2015 regarding the utility of DBS for patients with treatment-refractory depression. The literature review revealed that most DBS research is open label, with few large randomized, placebo-controlled trials to confirm results. Long-term response rates with DBS were between 40% and 70%, with clinical effects depending on location of electrode placement. Improvement was documented to last for months to years. Although DBS is potentially efficacious and a relatively safe option for patients with treatment resistance, it is invasive, costly, and still considered experimental. Understanding of the neurobiology of depression, the mechanism of DBS action, and biomarkers that may predict patient response remains obscure. Future research should contain careful design, including homogenous inclusion criteria and characterization of pretreatment patient mood, somatic complaints, and cognition; consistent outcome measures; monitoring of depressive symptoms at different brain-positioning targets across an adequate time course; and records of stimulus parameters. Abstract : Depression has a high lifetime prevalence and recurrence rate, with approximately 35% of affected patients experiencing treatment-refractory depression. These individuals should benefit from additional treatment options. Deep brain stimulation (DBS) is being investigated for its efficacy in treatment-refractory cases. Although potentially beneficial and relatively safe, it is invasive, expensive, and considered experimental. A review of open-label studies evidences promising results; however, DBS has not been confirmed by large randomized placebo-controlled trials. Long-term improvement is documented with sustained remissions. DBS may provide hope to depressed people with suboptimal treatment responses.